TEXT MESSAGE COMPRESSION ANALYSIS USING THE LZ77 ALGORITHM - Arjon Samuel Sitio (INFOKUM, 2018)
Data compression is a process for converting an input data stream (original data) into another data stream in the form of output or other (compressed) streams that have a smaller size. One of the main functions of data compression is to reduce the file size by replacing characters that are generally 8 bits in size with shorter codes. In data compression, many algorithms can be used to process input into the desired output, so it must be considered aspects such as compression ratio, space-saving, and compression speed of each algorithm.